A Concise Method for Synthesizing 1, 4, 8, 11‐Tetraaza‐6, 13‐dioxapentacene Derivatives. Issue 10 (11th June 2013) - Li, Gang; Long, Guankui; Chen, Wangqiao; Hu, Fangzhong; Chen, Yongsheng; Zhang, Qichun
Abstract A concise method for preparing five tetraazadioxaacene derivatives through condensation reactions between 2, 3, 7, 8‐tetraaminodibenzo‐1, 4‐dioxin tetrahydrochloride and commercially available diketones has been developed. The as‐prepared compounds have interesting photophysical and electrochemical properties. Cyclic voltammetry measurements demonstrate that compounds 4 and 5 have less negative reduction potentials, which is inconsistent with the results of DFT calculations, and both might be promising for use as active elements in organic electronics.